Biocompatible scaffolds constructed by chondroitin sulfate microspheres conjugated 3D-printed frameworks for bone repair. (1st January 2023) - Guo, Liangyu; Chen, Hao; Li, Yuanli; Zhou, Juan; Chen, Jinghua
Abstract: Most bone repair scaffolds are multi-connected channel structure, but the hollow structure is not conducive to the transmission of active factors, cells and so on. Here, microspheres were covalently integrated into 3D-printed frameworks to form composite scaffolds for bone repair. The frameworks composed of double bond modified gelatin (Gel-MA) and nano-hydroxyapatite (nHAP) provided strong support for related cells climbing and growth. Microspheres, which were made of Gel-MA and chondroitin sulfate A (CSA), were able to connect the frameworks like bridges, providing channels for cells migration. Additionally, CSA released from microspheres promoted the migration of osteoblasts and enhanced osteogenesis. The composite scaffolds could effectively repair mouse skull defect and improve MC3T3-E1 osteogenic differentiation. These observations confirm the bridging effect of microspheres rich in chondroitin sulfate and also determine that the composite scaffold can be as a promising candidate for enhanced bone repair.